2013
DOI: 10.1016/j.rmed.2013.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Age at asthma onset and subsequent asthma outcomes among adults with active asthma

Abstract: Summary Introduction Little is known about the extent to which the age at which asthma first began influences respiratory health later in life. We conducted these analyses to examine the relationship between age at asthma onset and subsequent asthma-related outcomes. Methods We used data from 12,216 adults with asthma who participated in the 2010 Behavioral Risk Factor Surveillance System Asthma Call-back Survey to describe the distribution of age at asthma onset. Linear regression was used to estimate asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 24 publications
3
33
0
4
Order By: Relevance
“…These sampling weights accounted for BRFSS and ACBS nonresponse and unequal sampling probabilities, as well as differences across states in the number of participating years during 2006–2010. 30, 31, 34 To properly account for the complex sample survey design, 33, 35 the entire dataset (N = 14,585 children ever diagnosed with asthma) was retained in the final analyses; only results generated from the stratum of the selected population of 8,881 children with current asthma attending school within the past 12 months (Figure 1) are presented. 35 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These sampling weights accounted for BRFSS and ACBS nonresponse and unequal sampling probabilities, as well as differences across states in the number of participating years during 2006–2010. 30, 31, 34 To properly account for the complex sample survey design, 33, 35 the entire dataset (N = 14,585 children ever diagnosed with asthma) was retained in the final analyses; only results generated from the stratum of the selected population of 8,881 children with current asthma attending school within the past 12 months (Figure 1) are presented. 35 …”
Section: Methodsmentioning
confidence: 99%
“…Variance under the sampling conditions (i.e., sampling with replacement) was estimated with the Taylor series method. 33, 36 For multivariate analyses, ORs, prevalence ratios (PRs; predicted marginal risk ratios) 30, 37 , and 95% CIs were calculated for associations between asthma-related school absenteeism and all dependent variables; these were adjusted for child age group, race/ethnicity, asthma medication use, and annual household income. Because many dependent variables were common (>10% prevalence in this study population) 38 , ORs were larger than PRs; therefore, this study highlights findings from PRs.…”
Section: Methodsmentioning
confidence: 99%
“…As in previous analysis of Asthma Call-back Survey data [32, 33], we categorized respondents as having active asthma if they reported that at least one of the following occurred during the past 12 months: talked to a doctor or other health professional about [his/her] asthma, took asthma medication, or experienced any symptoms of asthma. The remaining respondents, those without active asthma, are hereafter referred to as having inactive asthma.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluating the population with asthma is necessary to enact effective preventive measures and health policies to attenuate this burden, and various criteria have been developed by researchers to ascertain cases [417]. However, there is no uniform approach in identifying survey respondents with asthma, and the use of the differing classification criteria may have a substantial effect on prevalence estimates [18].…”
Section: Introductionmentioning
confidence: 99%
“…national surveys, such as the Behavioral Risk Factor Surveillance System (BRFSS) and the National Health Interview Survey, collect information on asthma to determine the prevalence and burden of the disease in specific populations and to guide public health efforts on alleviating the impact of asthma [21–23]. Using these survey data, two classifications of asthma status, current asthma and active asthma, were developed [416]. For example, persons with current asthma were survey respondents who have ever been told by a health professional they have asthma and still have asthma.…”
Section: Introductionmentioning
confidence: 99%